Method for preparing composite filter medium, and composite filter medium obtained by preparation method
By incorporating a degassing step to stabilize vacuum conditions, the method achieves complete polymerization and strong adhesion of plasma coatings on composite filter materials, enhancing water and oil repellency and maintaining high air permeability.
Patent Information
- Application Number
- JP2024230126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-10-19
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-10
AI Technical Summary
Existing composite filter materials face challenges in achieving optimal polymerization and adhesion of plasma coatings due to variations in vacuum chamber pressure, leading to incomplete coating polymerization and reduced water and oil repellency.
A method involving a preliminary degassing step to remove moisture from the filter material before plasma treatment, ensuring stable vacuum conditions for complete polymerization and strong adhesion of the coating on the nanofibers and base fabric.
The method results in a composite filter material with a fully polymerized coating that effectively repels water and oil, maintaining high air permeability and acoustic transmission while ensuring strong adhesion and improved cleaning ease.
Smart Images

Figure 2025060885000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing a composite filter material, and also to a composite filter material obtained by the method.
[0002] The field of the invention is that of composite filter materials, in particular those used for protection against the ingress of dust particles and for repelling liquids in general, such as water and oil, so as to ensure high air permeability, i.e. low acoustic impedance, for best sound transmission, for example in electroacoustic components of household appliances, in particular mobile phones. [Background technology]
[0003] Known composite filter materials are formed by combining at least one layer of nanofibers supported by a weft and warp backing, where the nanofiber layer is deposited on the backing by an electrospinning process and a plasma coating is applied to the backing and nanofibers, forming a composite filter material in which the nanofiber layer is attached to the backing.
[0004] To ensure the desired performance of plasma coating, it is essential that the monomer injected into the plasma system chamber polymerizes on the surface of the substrate and nanofibers under optimal conditions. However, this polymerization condition depends on the process parameters set for the plasma treatment, such as the power of the power supply, the sealed pressure in the vacuum chamber, the exposure time of the fibers to the plasma treatment, and the distance of the substrate from the electrode.
[0005] During the above-mentioned plasma treatment, the pressure in the vacuum chamber may fluctuate relative to the set value, and in particular, the pressure may increase due to gases released by the material being treated in the vacuum chamber. The reason for the increase in pressure in the chamber during plasma treatment to form coatings on the surface of substrates and nanofibers is mainly due to the moisture content of the material placed in the vacuum chamber. Indeed, during this treatment, water molecules are released from the textile material to be coated, causing an increase in pressure and mixing with and contaminating the coating plasma feed gas. This becomes even more of a problem when working with rolls of material with large diameters and weights, i.e., in industrial production processes.
[0006] Such an increase in pressure inevitably changes the polymerization conditions of the materials that form the base fabric and nanofiber coating, resulting in incomplete polymerization of the coating. As a result, the surface energy of the nanofibers cannot be reduced, and the desired water and oil repellency of the final filter material cannot be achieved.
[0007] Contamination of the coating plasma feed gas by water molecules released from the substrate alters the polymerization reaction, resulting in coatings with lower chemical and physical properties than the desired water- and oil-repellent coating performance, and inability to ensure sufficient adhesion of the polymerized coating to the substrate. Summary of the Invention [Means for solving the problem]
[0008] The main object of the present invention is to provide a composite filter material, and a method for its manufacture, which ensures optimal polymerization of the coating deposited on the surface of the monofilaments forming the substrate and on the surface of the nanofibers, compared to known filter materials of this type.
[0009] It is also an object of the present invention to provide a method for producing a filter medium having a coating that adheres strongly to the surface of the monofilaments of the substrate and to the surface of the nanofibers.
[0010] These and other objects are achieved by a method and a filter material, respectively, according to claims 1 and 10. Preferred embodiments of the invention will become apparent from the remaining claims.
[0011] Compared to known filter media, the filter media of the present invention offers the advantage of maintaining the desired level of water and oil repellency due to the formation of a fully polymerized coating that adheres strongly to the surface of the substrate and nanofibers.
[0012] The composite filter material of the present invention, in which the individual nanofibers and the individual threads of the fabric are covered with a thin, highly hydrophobic and oleophobic coating, has the ability to repel dirt and, in particular, liquids, particularly water (high surface tension, 72 mN / m), but also liquids with low surface tension (30-40 mN / m), such as oil. This property of the filter material of the present invention is particularly useful in applications as protective screens for electroacoustic components in mobile phones. In fact, the filter material of the present invention is composed of nanofibers that provide extremely high permeability to air (and extremely low acoustic impedance), thereby ensuring effective protection against the penetration of particles. Furthermore, due to its specific coating, the composite filter material of the present invention prevents the penetration of water, oil, and other types of liquids. In fact, the filter material of the present invention not only prevents the penetration of these liquids, but is also easier to clean due to its water-repellent properties. [Brief explanation of the drawings]
[0013] These and other objects, advantages and features will become apparent from the following description of preferred embodiments of the method and filter material of the present invention, illustrated by way of non-limiting example in the figures of the accompanying drawings.
[0014] [Figure 1] 1 is a cross-sectional schematic view of an example of a composite filter material of the present invention. [Figure 2] A detailed view of nanofibers deposited by electrospinning onto the corresponding yarns of the base fabric is shown. Both the nanofibers and the base fabric yarns are completely coated with a nanometer layer of water- and oil-repellent polymer applied by plasma treatment. [Figure 3] 1 illustrates an electrospinning method for fabricating the nanofiber layers of the filter material of the present invention. [Figure 4] 1 shows a schematic representation of the plasma treatment of a filter material of the invention obtained by depositing a nanofiber layer made by an electrospinning process on a substrate. [Figure 5] 1 shows the relationship between flow rate and pressure measured across the filter media for dry and wet samples. [Figure 6] The relationship between the removal pressure and the corresponding pressure drop is shown for clog removal tests performed on two different samples. DETAILED DESCRIPTION OF THE INVENTION
[0015] The composite filter material of the present invention, generally designated by the numeral 1 in Figure 1, comprises a support formed by a warp and weft type base fabric 2, preferably a monofilament fabric, on the surface of which nanofibers 4 are deposited by electrospinning. Monofilaments 3 made from monofilaments of polyester, polyamide, polypropylene, polyethersulfone, polyimide, polyamideimide, polyphenylene sulfide, polyetheretherketone, polyvinylidene fluoride, polytetrafluoroethylene, or aramid are suitable for the present invention, and the mesh openings of the base fabric 2 are in the range of 2500 microns to 5 microns.
[0016] The base fabric used to prepare the composite filter material of the present invention is selected from a wide range of synthetic monofilament fabrics, differing in the chemical properties of the monofilaments used in weaving, such as polyester, polyamide, polypropylene, polyethersulfone, polyimide, polyamideimide, polyphenylene sulfide, polyetheretherketone, polyvinylidene fluoride, polytetrafluoroethylene, aramid, etc. Also, the base fabric may have a woven structure of 4 to 300 threads / cm, a thread diameter of 10 to 500 microns, and a basis weight of 15 to 300 g / m. 2A base fabric having a weave of 18 to 1000 microns and a thickness of 18 to 1000 microns is suitable for the present invention. For finishing and further surface treatment, washed and heat-set "white" fabric, colored fabric, plasma-treated fabric, hydrophobic fabric, hydrophilic fabric, antibacterial fabric, antistatic fabric, etc., can be used, in addition to metallization. A polyester monofilament fabric with 48 threads / cm, a diameter of 55 μm, and a base fabric mesh opening of 153 μm is preferred for the present invention.
[0017] Nanofibers of polyester, polyurethane, polyamide, polyimide, polypropylene, polysulfone, polyethersulfone, polyamideimide, polyphenylene sulfide, polyetheretherketone, polyvinylidene fluoride, polytetrafluoroethylene, alginate, polycarbonate, PVA (polyvinyl alcohol), PLA (polylactic acid), PAN (polyacrylonitrile), PEVA (polyethylene vinyl acetate), PMMA (polymethyl methacrylate), PEO (polyethylene oxide), PE (polyethylene), PVC, PEI, PUR, and polystyrene are suitable for the present invention. These nanofibers can have diameters between 50 nm and 700 nm. PVDF (polyvinylidene fluoride) nanofibers with diameters in the range of 75 to 200 nm are preferred.
[0018] 3, the electrospinning process for the formation of nanofibers 4 and their subsequent deposition on the substrate 2 consists in ejecting the material for the formation of nanofibers 4, dissolved in a suitable solvent, through a nozzle 5 and spreading it on an electrode 6. Due to the potential difference between the nozzle 5 and the electrode 6, the nanofibers 4 are formed by the evaporation of the solvent by the electric field and the stretching of the polymer deposited on the electrode by the nozzle. The nanofibers thus formed are then stretched and subsequently deposited on the substrate 2.
[0019] The composite filter material thus obtained is then surface treated by plasma deposition of a nanometer-thick polymer layer 7 onto the exposed surfaces of the fabric 2 and nanofiber layer 4, completely covering the outer surfaces of the monofilaments 3 of the base fabric 2 and the aforementioned nanofibers 4 (Figure 2).
[0020] As shown in Figure 4, the composite filter material 8 obtained from the preceding electrospinning process of Figure 3 is placed inside a plasma treatment chamber 9 in the presence of a gas that forms the above-mentioned coating 7 over the composite filter material 1 of the present invention.
[0021] Gases based on fluorocarbon acrylates are preferred for the present invention, especially heptadecafluorodecyl acrylate, perfluorooctyl acrylate, etc. The advantage of the present invention is that the gases form fluorocarbon acrylate deposits upon plasma treatment with water and oil repellency.
[0022] In the above-mentioned plasma treatment, a carrier gas is also used, for example a carrier gas of the type described in WO2011089009.
[0023] The above-mentioned plasma treatment involves the creation of a vacuum of 10 to 50 mTorr, an electrode power of 150 to 350 W, and an exposure time of 0.5 to 6 minutes.
[0024] Coatings deposited by plasma technology can be up to 500 nm thick and, depending on the specific technology used, have the structure of a continuous film that can coat even 3D surfaces such as fabrics. Depending on the compounds used, these coatings can have a variety of specific properties, such as hydrophobicity, oleophobicity, hydrophilicity, and antistatic properties.
[0025] Coatings obtained starting from the following compounds in the starting gas are preferred for the invention: 1H,1H,2H,2H-Heptadecafluorodecyl acrylate (CAS number: 27905-45-9, H2C=CHCO2CH2CH2(CF2)7CF3) 1H,1H,2H,2H-Perfluorooctyl acrylate (CAS number: 17527-29-6, H2C=CHCO2CH2CH2(CF2)5CF3)
[0026] The thickness of the coating 7 is 15 to 60 nm, which is suitable for preventing the composite filter material 1 from excessively narrowing the pores formed in both the fabric 2 and the nanofibers 4, thereby hindering the free passage of sound.
[0027] The composite filter material 8 resulting from the electrospinning process of FIG. 3 was tested and compared to a similar composite filter material 1 with subsequent plasma treatment of FIG.
[0028] In particular, the above-mentioned filter material 8 is formed by a weft and warp fabric made of synthetic monofilaments 3 (e.g. of polyester), on which nanofibers 4, also made of synthetic material (e.g. polyester), are deposited so as to obtain an acoustic impedance of 25 MKS Rayl, as measured, for example, with a Textest instrument for measuring acoustic impedance / air permeability.
[0029] After plasma treatment of the filter material 8, it can be observed that for the composite filter material 1 of the invention the acoustic impedance remains unchanged at a value of 25 MKS Rayl. 5,200 l / m at a pressure of 200 Pa 2 The air permeability and filtering efficiency also remain unchanged.
[0030] On the other hand, a significant increase was observed in both the contact angle with water (50°-130°) and the contact angle with oil (50°-120° for oils including corn oil with a surface tension of 32 mN / m), where the contact angle is measured for a water or oil droplet on nanofiber 4 using the sessile drop method (deposition of a droplet and measurement of the contact angle with a high-resolution camera) on a Kruss instrument.
[0031] Clogging removal test To provide evidence for the above observations, a test method was developed to numerically quantify the energy required to remove oil from the surface of the composite filter media of the present invention.
[0032] This test was performed using a PMI 1200 porometer, an instrument that uses capillary flow porometry to determine the bubble point, minimum pore size, and pore size distribution of a tested sample. Capillary flow porometry, or simply porometry, is based on a very simple principle: measuring the gas pressure required to force a wetting liquid through the pores of a material. The pressure at which the pores empty is inversely proportional to the size of the pores themselves. Larger pores require lower pressures, while smaller pores require higher pressures.
[0033] The test consists of cutting the sample to be analyzed and placing it in the test chamber. The sample is then held in place by an O-ring in a manner that ensures the absence of lateral air leaks. Once the chamber is closed, the air permeability of the filter material is measured, and a curve (the drying curve in the graph in Figure 5) is obtained that relates the air flow through the sample to the pressure drop measured across the filter material. After the drying curve is obtained, the test chamber is opened, and while the sample remains in place, its surface is covered with a test liquid with a low surface tension (typically <20 mN / m). The test chamber is then closed, and the air permeability of the material is measured again. When the material is occluded by the test liquid, the pressure increases, but no air flow is measured downstream until the pressure is high enough to push the liquid through the pores. From this moment on, increasingly smaller pores become empty as the pressure increases until the (previously wet) sample is completely dried and the two curves in Figure 5 overlap. The details of the analysis will not be discussed, but on a qualitative level, the difference between the two curves allows the bubble point value (largest pore), the size of the smallest pore, and the pore size distribution to be determined.
[0034] In a specific instance, this test was performed using corn oil (surface tension 32 mN / m) in place of the test liquid to determine oil repellency / removal ability.
[0035] The graph in Figure 6 shows the removal pressure and the corresponding pressure drop (energy required for removal). The samples considered in the graph in Figure 6 are filter material 8 from the electrospinning process (curve 10) and filter material 1 of the present invention (curve 11). It can be seen that filter material 1 of the present invention can remove oil at a significantly lower pressure than composite filter material 8 that has not been subjected to plasma treatment, or that a significantly greater amount of oil is removed at the same pressure.
[0036] According to the present invention, it has now surprisingly been found that by adding to the above-described method a preliminary step of degassing the materials forming the monofilaments 3 and nanofibers 4 of the composite filter material 8, which are processed in a vacuum chamber, and a subsequent plasma treatment prior to the step of forming the coating 7, complete polymerization and strong adhesion of the coating subsequently deposited on the monofilaments forming the substrate and on the nanofibers is achieved.
[0037] In particular, according to the present invention, prior to the plasma coating 7 formation step, a degassing step is performed in chamber 9 on the filter material 8 obtained by the electrospinning process, so that the pressure in chamber 9 is adjusted to a value between 5 and 250 mTorr. For this purpose, a degassing step should be performed with an exposure time typically ranging from 5 seconds to 5 minutes, depending on the size, weight, and hygroscopicity of the material being processed. Of course, once an appropriate exposure time is determined to allow complete drying of the substrate—i.e., a time that ensures a stable vacuum for the subsequent coating step—the appropriate speed for the degassing step must be set depending on the exposure area within the chamber. This area is defined by the distance between the unwinding and winding cylinders and the size of the electrodes. In particular, if the material is in roll form, it will be continuously unwound and wound in chamber 9 at a speed between 0.1 and 50 m / min, depending on the moisture content of the material. Chamber 9 is equipped with an opening appropriately controlled by a valve system, through which gases to be removed can be evacuated.
[0038] According to the present invention, the pre-check of the pressure value allows the moisture contained in the material to be treated in the chamber 9 to be completely removed so that the desired polymerization pressure of the coating 7 on the surface of the base fabric and nanofibers can be reached in the subsequent coating formation process.
[0039] Furthermore, according to the present invention, after the degassing treatment and before the step of forming the coating 7, the surfaces of the monofilaments 3 and nanofibers 4 forming the substrate 2 can be reactivated in chamber 9 by a plasma treatment carried out in chamber 9, preferably with a carrier gas selected from nitrogen, helium, argon, and oxygen, maintained at a pressure of 10 to 400 mTorr, an electrode power in the range of 100 to 2000 W, and an exposure time in the range of 5 seconds to 5 minutes. Depending on the gas, exposure time, and power used, a more or less pronounced etching effect can be obtained, resulting in the formation of nanometer / micrometer roughness on the treated surface.
[0040] In this process, no coating is formed on the treated surface due to the absence of polymerizable monomers. Instead, ions from the carrier gas, sufficiently energized by the plasma, collide with the substrate surface with some energy, creating nanogrooves and thus nanometer-sized roughness, which promotes the grip and adhesion of the polymer coating 7 to the surface of the monofilaments 3 and nanofibers 4, significantly contributing to the repulsion of the filter material against water and oily liquids.
[0041] The results provided by the filter material formed by the manufacturing method of the present invention are shown in the following table, the values being measured on a filter material having a layer 7 of polymer material obtained after the plasma treatment for forming the latter: a degassing step during which the material to be treated is kept in the chamber 9 for 30 seconds, suitable to ensure a stable pressure of 25 mTorr for the subsequent treatment; a subsequent plasma treatment of the material to be coated, carried out in the presence of helium as carrier gas, at a vacuum of 150 mTorr, an electrode power of 600 W and an exposure time of 1 minute.
[0042] [Table 1]
[0043] These results show how the polymer coating 7 formed in the vacuum chamber 9 after the degassing step and the preceding plasma treatment ensures for the filter material of the present invention a very high contact angle with oil (>110°) and a much higher than minimum required adhesion level to the substrate.
[0044] The invention as described above and illustrated in the accompanying drawings may be modified to produce variations that fall within the scope of the appended claims.
[0045] In particular, if the filter material is made starting from a slightly hygroscopic material and subjected to a plasma deposition process, the reactivation step can be carried out solely by plasma treatment, again with a carrier gas selected from nitrogen, helium, argon and oxygen. In fact, for this type of slightly hygroscopic material, the above-mentioned preliminary degassing step can be omitted.
Claims
1. A method for producing a composite filter material (1), comprising the steps of: depositing nanofibers (4) onto a substrate (2) by an electrospinning process to form a first filter material (8); and coating the filter material (1) by plasma deposition of a coating (7) onto the first filter material (8) in a vacuum chamber (9); 10. A method for producing a composite filter material, characterized in that the method comprises, after the electrospinning process and prior to plasma deposition of the coating (7), a degassing step and a prior plasma treatment of the base fabric (2) and nanofibers (4) forming the first filter material (8) in the same chamber (9).
2. 2. A method according to claim 1, characterized in that during the degassing step, the chamber (9) is brought to an internal pressure value between 5 and 250 mTorr.
3. 2. The method according to claim 1, characterized in that during the degassing step, an exposure time of between 5 seconds and 5 minutes is ensured for the first filter material (8) in the chamber.
4. 2. The method according to claim 1, further comprising, after the degassing step and before the plasma deposition of the coating (7), a step of forming irregularities on the surface of the base fabric (2) and the nanofibers (4), the step of forming irregularities being carried out in the chamber (9) in the presence of a carrier gas and without a polymer-containing gas by plasma treatment of the first filter material (8) obtained in the degassing step.
5. 5. The method of claim 4, wherein the carrier gas is selected from nitrogen, helium, argon, or oxygen.
6. A method according to claim 5, characterized in that the plasma treatment is carried out in a chamber (9) at a pressure between 10 and 400 mTorr, with an electrode power between 100 and 2000 W and an exposure time between 5 seconds and 5 minutes.
7. 2. The method according to claim 1, characterized in that the electrospinning process comprises the extrusion of a polymer dissolved in a suitable solvent through a nozzle (5) followed by drawing the fibers between the nozzle itself and an electrode, thereby obtaining a deposition of nanofibers (4) on the base fabric suitably interposed between the nozzle and the electrode, and then the filter material (8) thus obtained is subjected to a surface treatment by plasma deposition of a nanometer-thick polymer layer (7) on the exposed surfaces of the base fabric (2) and the layer of nanofibers (4), to obtain the composite filter material (1) in which the external surfaces of the monofilaments (3) of the base fabric (2) and of the nanofibers (4) are coated with the polymer layer (7).
8. 8. The method of claim 7, wherein the plasma deposition process comprises forming a vacuum of 10-50 mTorr, an electrode power of 150-350 W, and an exposure time of 0.5-6 minutes.
9. A method for producing a composite filter material (1), comprising the steps of: depositing nanofibers (4) onto a substrate (2) by an electrospinning process to form a first filter material (8); and coating the filter material (1) by plasma deposition of a coating (7) onto the first filter material (8) in a vacuum chamber (9); 4. A method for producing a composite filter material, comprising the steps of: forming irregularities on the surfaces of the base fabric (2) and the nanofibers (4) by plasma treatment of the first filter material (8) in the presence of a carrier gas and in the absence of a polymer-containing gas in the chamber (9) after the electrospinning process and prior to plasma deposition of the coating (7).
10. A composite filter material of the type comprising a substrate (2) on which nanofibers (4) are deposited, A composite filter material, characterized in that the base fabric and the nanofibers are covered with a nanometric coating layer (7), and the base fabric (2) and the nanofibers (4) have nanogrooves.
11. 11. The filter material according to claim 10, characterized in that the coating (7) is formed by a film having a thickness of at most 500 nm.
12. 11. The filter material of claim 10, wherein the coating (7) is a fluorocarbon acrylate-based coating having water- and oil-repellent properties.
13. The filter material according to claim 10, characterized in that the base fabric (2) is a monofilament fabric made from monofilaments of polyester, polyamide, polypropylene, polyethersulfone, polyimide, polyamideimide, polyphenylene sulfide, polyetheretherketone, polyvinylidene fluoride, polytetrafluoroethylene, or aramid.
14. The filter material according to claim 10, characterized in that the base fabric (2) has mesh openings of 2500 to 5 microns.
15. The base fabric (2) has a woven structure with 4 to 300 threads / cm, a thread diameter of 10 to 500 microns, and a basis weight of 15 to 300 g / m 2 11. The filter media of claim 10, having a weave of: and a thickness of 18 to 1000 microns.
16. The nanofibers (4) may be made of polyester, polyurethane, polyamide, polyimide, polypropylene, polysulfone, polyethersulfone, polyamideimide, polyphenylene sulfide, polyetheretherketone, polyvinylidene fluoride, polytetrafluoroethylene, alginate, polycarbonate, PVA (polyvinyl alcohol), PLA.
11. The filter material of claim 10, which is a nanofiber of polylactic acid, polyacrylonitrile, polyethylene vinyl acetate, PMMA, polyethylene oxide, PE, PVC, PI, or polystyrene.
17. 11. The filter material of claim 10, wherein the nanofibers (4) are PVDF (Polyvinylidene Fluoride) nanofibers with a diameter between 50 nm and 700 nm.
18. Use of the filter material according to any one of claims 10 to 17 for the protection of electro-acoustic components in a mobile phone.